Compensatory Annulment Justice in Indonesian Marriage Law: Coercion, Cohabitation, and Substantive Protection - Nur, Muliadi; Bukido, Rosdalina; Subeitan, Syahrul Mubarak (Kosmik Hukum, 2026)
Existing scholarship on marriage annulment in Indonesian family law primarily addresses formal defects of validity and coercion, but offers limited analysis of compensatory remedies when annulment produces social and economic harm. This article addresses that gap by examining Decision No. 42/Pdt.G/2023/PA.Llk and introducing the concept of compensatory annulment justice, defined as a judicial approach that annuls a coerced marriage while preserving limited remedies for relational harm. Using a normative juridical, case-based analysis, the study treats the decision as primary legal material to assess judicial reasoning on consent, coercion, cohabitation, and compensation. The findings show that the court moved beyond formal validity by (i) construing coercion through witness-based proof of psychological threat, (ii) positioning premarital cohabitation and local custom as relevant social facts without allowing them to override free consent, and (iii) awarding Rp2,000,000 via reconventional claim grounded in unlawful act doctrine and proportionality. These results demonstrate that annulment need not erase all consequences of the relationship. The study contributes a coherent framework for integrating consent protection with post-annulment responsibility, offering doctrinal guidance for courts to balance autonomy, legal pluralism, and substantive justice in family disputes.